The coping strategies employed by individuals with chronic low back pain: secondary qualitative analysis of data from diverse adult populations in two sub-Saharan African countries - Igwesi-Chidobe, Chinonso Nwamaka; Nkhata, Loveness A.; Ozumba, Benjamin (Frontiers in Rehabilitation Sciences, 2024)
IntroductionThe use and influence of coping mechanisms vary across cultures and evaluation methods. Limited research exists on coping mechanisms for non-specific chronic low back pain (CLBP) in African societies. This secondary qualitative study explored adaptive and maladaptive coping strategies used by adults with CLBP in Nigerian and Zambian communities.MethodsPrimary qualitative data from studies in rural Nigeria and peri-urban Zambia were used. Primary data were collected through in-depth face-to-face interviews with adults living with back pain to explore their experiences and coping strategies. Thematic analyses of interview transcripts from both studies were conducted using the framework approach, combining inductive and deductive analysis techniques.FindingsParticipants used a mix of adaptive and maladaptive coping strategies for CLBP. Some strategies had both positive and negative aspects, with varying effects on individuals. A few participants focused on adaptive coping, staying positive, and actively managing their pain through stretching, exercise, pacing activities, spirituality, and belief in their strategies. They avoided seeking treatment for their back pain.DiscussionThe nuances in coping with CLBP should be taken into consideration when developing coping assessment strategies and rehabilitation interventions for individuals with CLBP.